PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP LITERASI MATEMATIKA SISWA KELAS VII SMPN 20 SELUMA - Putri, Cindy Samya; Haji, Saleh (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The aim of this research is to determine the effect of the Problem Based Learning learning model on the mathematical literacy abilities of Class VII students at SMPN 20 Seluma. The research method used in this research is the analytical method. The type of research carried out was a quasi-experimental design with The Nonequivalent Posttest-only Control Group Design. In this study, the population was all class VII students at SMPN 20 Seluma with two sample classes selected using the purposive sampling technique. The sample class is the experimental class, namely Class VIIB, with 15 students with Problem Based Learning and the control class, namely Class VIIA, with 15 students with expository learning. This research instrument is a test of mathematical literacy skills which consists of formulating problems (formulate), applying concepts (employee), and interpreting the results of the solution. This test was carried out after the learning model was applied to both sample tests (posttest). The post-test results in the experimental class with Problem Based Learning obtained an average student score of 71.33, while in the control class with expository learning the average student score was 60.67. Data analysis was carried out using an independent t-test on the post-test results with a significant level of sig. (2-tailed) = 0.046 < significant level (and which shows that there is a difference between the results of mathematical literacy abilities between students with Problem Based Learning and expository learning. The results of the research can be concluded that there is an influence of the Problem Based Learning learning model on the mathematical literacy abilities of Class VII students at SMPN 20 Seluma